“The First Wave”: The Shibanid dominance in the Lower Volga region in 1361–1367 - Grinberg M. (Золотоордынское обозрение)
Abstract: Objective: To continue the study of the role of the Shibanids in the initial and part of the middle period of the era of “the Great Troubles” in the Golden Horde, which began in the previous article with the study of the role of the first Shibanid khan – Khizr. This article discusses the rule of the following three khans, who with varying degrees of probability can be attributed to the Shibanids – Murid (brother of Khizr), Khayr-Pulad and Aziz Shaykh. Research materials: The main written sources used in the article are Russian chronicles and late (in relation to the period of research) Chinggisid genealogical writings (mainly from Central Asia). The work of the Timurid court historian Muin al-Din Natanzi should be added. However, the information ин these sources is rather scarce on many issues for this period, and numismatic material and (to a less degree) archaeological data were widely used to expand the amount of information on the studied topic. Research results and novelty: The role of the Shibanids was examined in more detail, clarified, and specified. This is especially true for Murid, whose rule is very important for the initial period of the “Great Troubles”. As it turned out, he was trying to create a new administrative centre for himself in Gulistan, while, in many ways, continuing the policy of the Batuids, but not of his perished brother. It was also attempted to clarify, as much as possible in absence of narrative and documentary sources, the causes and the outlines of Khayr Pulad’s policies, known to us only from the numismatic data. In addition, some features of the policies of Aziz Shaykh towards the Russian principalities were explained. One of the important results of the study is the conclusion that the aforementioned Shibanid khans came from three different genealogical branches of Shiban’s descendants, and these branches varied in their importance.